2021
DOI: 10.3354/meps13697
|View full text |Cite
|
Sign up to set email alerts
|

Twilight foraging enables European shags to survive the winter across their latitudinal range

Abstract: Species breeding at high latitudes face a significant challenge of surviving the winter. Such conditions are particularly severe for diurnal marine endotherms such as seabirds. A critical question is therefore what behavioural strategies such species adopt to maximise survival probability. We tested 3 hypotheses: (1) they migrate to lower latitudes to exploit longer day length (‘sun-chasing’), (2) they forage at night (‘night-feeding’), or (3) they target high-quality food patches to minimise foraging time (‘f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…S4). Similar observations were made for European shags in the Norwegian and Barents Seas (Moe et al 2021 Theme Section). Latitude may also indirectly reflect prey availability via changes in primary productivity.…”
Section: Broad-scale Migratory Movementssupporting
confidence: 81%
“…S4). Similar observations were made for European shags in the Norwegian and Barents Seas (Moe et al 2021 Theme Section). Latitude may also indirectly reflect prey availability via changes in primary productivity.…”
Section: Broad-scale Migratory Movementssupporting
confidence: 81%
“…between‐year variance in lay date within a population, after all other terms have been taken into account) greatly exceeded the levels estimated for other species in the analysis (Table 3). European shags are partial migratory whereby a proportion of the population remain resident at the breeding colonies throughout the year, and most migrant individuals make shorter distance movements than the other study species (Grist et al, 2014; Moe et al, 2021), so may be more sensitive to local conditions, such as abundance of forage fish (Lorentsen et al, 2015) and have an unusually high capacity to adjust laying dates accordingly. While auk populations in our analysis do remain in the North Atlantic over winter and spring, many migrate to a variety of different areas (Fayet et al, 2017; Frederiksen et al, 2016), although it should be noted that synchronised survival in Atlantic puffin has been attributed to an overlap in non‐breeding grounds of some Norwegian populations used in this analysis (Reiertsen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies has demonstrated a large variation in migration strategies, routes and destinations between and within populations of the same North Atlantic seabird species (Frederiksen et al 2012, Dean et al 2015, Fayet et al 2017a, van Bemmelen et al 2017, Merkel et al 2021a, 2021b in this Theme Section, Moe et al 2021). For example, in 2 sympatric meta-populations of common and Brünnich's guillemots in the Northeast Atlantic, Merkel et al (2021b) showed that different breeding populations had specific non-breeding habitats implying a strong migratory connectivity.…”
Section: Migratory Connectivitymentioning
confidence: 99%
“…These seabirds are generally diurnal and visual predators such that finding food when there is no or very little light may prove challenging. European shags Phalacrocorax aristotelis, for example, survive such conditions in northern Norway by concentrating their foraging during the available twilight (Moe et al 2021 in this Theme Section). Twilight foraging has also been observed in great cormorants Phalacrocorax carbo and Steller's eiders Polysticta stelleri in northern Norway, where they adjust their foraging times towards midday as winter progresses (Johansen et al 2001, Systad & Bustnes 2001.…”
Section: Migration Strategies and Non-breeding Movementsmentioning
confidence: 99%